ANTHROPOGENIC POLLUTION OF SOIL WITH COPPER AND THE PHYTOREMEDIATION POTENTIAL OF DIFFERENT AGRICULTURAL CROPS - S. G. Veliksar; S. S. Lisnik; D. N. Bratco; S. I. Toma (Труды по прикладной ботанике, генетике и селекции)
The results of the conducted studies have shown that an excess of copper in the soil contributes to an increase of its accumulation in the soil and plant organs, which has a negative effect on plant growth and other metabolic processes, and impedes the transport of Fe, Mn and Zn in the aerial organs. Using the Cu-accumulating plants - alfalfa, clover, rape, and calendula - is one of the most promising elements of the technology of Cu phytoextraction from the soil. Two soybean varieties more tolerant to copper excess in the environment have been identified - ‘Dorintsa’ and ‘Horbovyanka’. They can be grown on soils with a high content of copper (after stubbing of perennial plants).